PERSEPSI ANAK USIA DINI TERHADAP BENTUK MAKANAN UNIK - Farida Arinie Soelistianto; Martono Dwi Atmadja; Kristina Widjajanti; Yani Ratnawati; Azam Muzakhim Imammuddin (Jurnal Pengabdian Polinema Kepada Masyarakat, 2021)
Nutrient content and efficacy of the oyster mushroom has a high protein with a complete amino acids, including essential amino acids needed manusia.Selain itutuna oyster contains vitamins B1, B2 and some mineral salts of the elements Ca, P, Fe, Na and K . The fiber content of 7.4% until the mushrooms start of 27.6% is very good for digestion. While the meatballs are generally the typical food of the city of Malang are usually made from raw material although recent beef can also be made from raw materials of fish, chicken and mushroom. Apart easily cultivated oyster mushrooms also are cheap and plentiful and can be purchased at any place. Communities with lower economic levels can utilize adequate nutrition by consuming the mushrooms. Making meatballs from the basic ingredients of oyster mushrooms are also very easy to manufacture so diharapkakn could be an alternative to improve nutrition can also be developed to increase revenues when produced as meatballs mushrooms. Pre-test results showed that before the training participants still do not understand about the material with a mean value of 1.92. After carrying out training post test mean value becomes 3.75 This means participants' understanding of the material provided increased 98.5135%. This shows that the community service activities managed to improve the knowledge and skills of participants in the process recipe meatballs made from fresh oyster mushrooms.